2012
DOI: 10.1364/ol.37.002289
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser fabrication of phase-shifted Bragg grating waveguides in fused silica

Abstract: Phase-shifted Bragg grating waveguides (PSBGWs) were formed in bulk fused silica glass by femtosecond laser direct writing to produce narrowband (22±3)  pm filters at 1550 nm. Tunable π and other phase shifts generated narrow passbands in controlled positions of the Bragg stopband, while the accurate placement of multiple cascaded phase-shift regions yielded a rectangular-shaped bandpass filter. A waveguide birefringence of (7.5±0.3)×10(-5) is inferred from the polarization-induced spectral shifting of the PSB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…5(a)) show a strong and narrow Bragg response seen only in reflection while the strong cladding mode coupling is seen only in transmission. The 3 dB bandwidth of 0.56 nm as seen in reflection is 2.8× larger than that reported for BGWs fabricated with a 0.55 NA lens [25,30]. This broadening may be due to an increased grating strength with higher resolution focusing, but waveguide birefringence is also a contributing factor.…”
Section: Optical Edge Filter Waveguidementioning
confidence: 68%
“…5(a)) show a strong and narrow Bragg response seen only in reflection while the strong cladding mode coupling is seen only in transmission. The 3 dB bandwidth of 0.56 nm as seen in reflection is 2.8× larger than that reported for BGWs fabricated with a 0.55 NA lens [25,30]. This broadening may be due to an increased grating strength with higher resolution focusing, but waveguide birefringence is also a contributing factor.…”
Section: Optical Edge Filter Waveguidementioning
confidence: 68%
“…Grenier et al demonstrated passband control using various phase shift values located in the centre of a WBG (Figure 18) [76]. The narrow transmission band of the π phase-shifted WBG had a contrast of 15 dB in reflection and a 3 dB bandwidth of 22 pm (quality factor Q = 70,455) but could only be observed under polarised probing due to WBG birefringence.…”
Section: Phase Shiftedmentioning
confidence: 99%
“…[1] Of special interest are integrated photonic elements like Bragg grating waveguides (BGW). Fs laser direct-written BGW have been realized as laser mirrors, spectral filters for wavelength multiplexing, or sensing elements for strain and temperature [1][2][3][4][5]. For the realization of such BGW, a periodic modulation of the refractive index in the waveguide has to be generated with the fs laser.…”
mentioning
confidence: 99%
“…In opposition to the former techniques, one "volume dot" is written by a burst of pulses, consisting of thousands of pulses, causing a higher refractive index change, and high reflecting first-order BG (89% reflectivity) were fabricated in fused silica. Even most promising and used for several applications [1,3,9], the burst writing technique of Zhang et al [8] still lacks in flexibility on the desired waveguide cross-section, which depends on parameters such as pulse energy, repetition rate, and focal length of the microscope objective. An alternative technique to produce a defined cross-section of a waveguide is the multiscan technique, which was applied successfully by different groups [5,10,11].…”
mentioning
confidence: 99%